Степаненко С.В. Сучасні технології на ринку інновацій - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
Issues related to the research of innovation potential and its in uence on economic development are considered. In particular, they determine modern approaches to assessing the effectiveness of evaluating innovation and methodical provision of innovation activities.